ADAT DAYAK DAN IMAN KRISTEN DALAM PENERAPANNYA DI TENGAH MASYARAKAT - Markus Amid (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Adat is a way of life that has been passed down from generation to generation, sometimes considered sacred, so that when religion with rules/teachings that are considered new by the community becomes a new way of life, it becomes a problem to be considered as throwing away custom, or people who have forgotten the land, or are arrogant. , fanatic or dubbed uncivilized. From a religious perspective, Christians are divided into several interpretations. The attitude of rejection, which considers customs a sin with the assumption that everything in the world is sin (1 John 2:15-16). Meanwhile, other interpretations are fully accepting of adat. Custom is a gift from God, the fall of man into sin has damaged and confused traditional values, customary values need to be tested with the Word of God. This study uses a qualitative methodology with an interview and literature approach. The result of the research is that Christians should not reject customs, they only need to sort out what is contrary to God's word and what is not contrary to God's word. Customs that are contrary to God's word must be abolished, while customs related to God's word must be cultivated. Conclusion: Christian faith must be above customs because Christian faith is directly related to faith in Christ